Description of Family Support and Anxiety Levels of Third Trimester Pregnant Women during the Covid-19 Pandemic in Tuban Regency - Lutfiya Dwinanda; Teresia Retna P; Yasin Wahyurianto (Universitas Islam Balitar, 2023)
The COVID-19 pandemic will pose a risk of contracting the virus to pregnant women and can affect their level of anxiety. Purpose of this study was to determine family support and anxiety levels of third trimester pregnant women during the COVID-19 pandemic, precisely at BPM Mujiati, Semanding District, Tuban Regency using a cross-sectional approach. Population in this study were all third trimester pregnant women who were examined at BPM Mujiati as many as 102 mothers, with a sample size of 81 mothers. The sampling technique used was a purposive sampling technique using a questionnaire sheet instrument. The results showed that almost all of the third trimester pregnant women (96.3%) received good family support, most of the third trimester pregnant women (65.4%) experienced mild anxiety levels, and most of the third trimester pregnant women (66.7%) received good family support. experienced mild anxiety. The right effort to minimize the anxiety of pregnant women is to provide maximum family support to pregnant women to reduce the risk of premature birth, postpartum depression and child care. Keyword : Anxiety, Covid-19, Family Support, Pregnancy